1998
DOI: 10.1029/98ja02297
|View full text |Cite
|
Sign up to set email alerts
|

Observations of solar wind directly driven auroral electrojets and gravity waves

Abstract: Abstract. One of principal objectives in studies of atmospheric gravity waves is to identify their sources. It has been hypothesized for many years that variations of the interplanetary magnetic field (IMF) can result in occurrence of the auroral electrojets in the high-latitude ionosphere and the auroral electrojets can generate gravity waves, but identification of this relationship in experiments has been difficult since gravity waves are generally observed far from the source region. In this paper, we prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 26 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Some earlier studies, focusing at higher magnetic latitudes, have suggested a close causal relationship between solar wind‐magnetosphere‐ionosphere (SW‐M‐I) coupling and MSTID occurrence [e.g,. Huang et al , ; Sofko and Huang , ]. Samson et al [] suggested that MSTIDs at high latitudes were likely to be related to Earth‐reflected AGW produced by Lorentz forcing or Joule heating of the atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…Some earlier studies, focusing at higher magnetic latitudes, have suggested a close causal relationship between solar wind‐magnetosphere‐ionosphere (SW‐M‐I) coupling and MSTID occurrence [e.g,. Huang et al , ; Sofko and Huang , ]. Samson et al [] suggested that MSTIDs at high latitudes were likely to be related to Earth‐reflected AGW produced by Lorentz forcing or Joule heating of the atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…If there are gravity waves generated in the auroral zone, the Super Dual Auroral Radar Network (SuperDARN) should be able to register the wave signature. In particular, Huang et al [1998] reported that quasiperiodic southward turnings of the IMF could result in a series of gravity wave pulses in the dayside high‐latitude ionosphere, and Huang et al [2000] found that the high‐latitude gravity waves may be related to internal magnetospheric oscillations during northward IMF. However, we checked the SuperDARN data in the present cases and did not find periodic gravity wave signatures at high latitudes poleward of Millstone Hill.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to point (ii), for example, several authors have shown that fluctuations in the IMF appear to drive Pc6/Pc7 band oscillations in the magnetosphere and ionosphere [e.g., Huang et al , ; Stephenson and Walker , ; Walker , ]. Kepko et al [] also showed observations that suggested that such oscillations can also be driven by solar wind density structures.…”
Section: Discussionmentioning
confidence: 99%